Systemic ablation of vitamin D receptor leads to skeletal muscle glycogen storage disorder in mice. Issue 1 (8th December 2021) - Das, Anamica; Gopinath, Suchitra D.; Arimbasseri, Gopalakrishnan Aneeshkumar
Abstract: Background: Vitamin D deficiency leads to pathologies of multiple organ systems including skeletal muscle. Patients with severe vitamin D deficiency exhibit muscle weakness and are susceptible to frequent falls. Mice lacking a functional vitamin D receptor (VDR) develop severe skeletal muscle atrophy immediately after weaning. But the root cause of myopathies when vitamin D signalling is impaired is unknown. Because vitamin D deficiency leads to metabolic changes as well, we hypothesized that the skeletal muscle atrophy in mice lacking VDR may have a metabolic origin. Methods: We analysed wild‐type (WT) mice as well as vitamin D receptor null (vdr−/−) mice for skeletal muscle proteostasis, energy metabolism, systemic glucose homeostasis, and muscle glycogen levels. Dysregulation of signalling pathways as well as the glycogen synthesis and utilization machinery were also analysed using western blots. qRT–PCR assays were performed to understand changes in mRNA levels. Results: Skeletal muscles of vdr−/− exhibited higher expression levels of muscle‐specific E3 ubiquitin ligases and showed increased protein ubiquitination, suggesting up‐regulation of protein degradation. Foxo1 transcription factor was activated in vdr−/− while Foxo3 factor was unaffected. Fasting protein synthesis as well as mTORC1 pathways were severely down‐regulated in vdr−/− mice. Skeletal muscle ATP levels were low in vdr−/− (0.58 ± 0.18 μmol/mL vs. 1.6 ± 0.0.14 μmol/mL, P  = 0.006), leading to increased AMPK activity. Muscle energy deprivation was not caused by decreased mitochondrial activity as we found the respiratory complex II activity in vdr−/− muscles to be higher compared with WT (0.29 ± 0.007 mU/μL vs. 0.16 ± 0.005 mU/μL). vdr−/− mice had lower fasting blood glucose levels (95 ± 14.5 mg/dL vs. 148.6 ± 6.1 mg/dL, P  = 0.0017) while they exhibited hyperlactataemia (7.42 ± 0.31 nmol/μL vs. 4.95 ± 0.44 nmol/μL, P  = 0.0032), suggesting systemic energy deficiency in these mice. Insulin levels in these mice were significantly lower in response to intraperitoneal glucose injection (0.69 ± 0.08 pg/mL vs. 1.11 ± 0.09 pg/mL, P  = 0.024). Skeletal muscles of these mice exhibit glycogen storage disorder characterized by increased glycogen accumulation. The glycogen storage disorder in vdr−/− muscles is driven by increased glycogen synthase activity and decreased glycogen phosphorylase activity. Increased glycogenin expression supports higher levels of glycogen synthesis in these muscles. Conclusions: The results presented show that lack of vitamin D signalling leads to a glycogen storage defect in the skeletal muscles, which leads to muscle energy deprivation. The inability of vdr−/− skeletal muscles to use glycogen leads to systemic defects in glucose homeostasis, which in turn leads to proteostasis defects in skeletal muscles and atrophy.